2019
DOI: 10.1128/aem.00105-19
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Quorum Sensing and Virulence in Burkholderia cenocepacia by a Structural Analogue of the cis -2-Dodecenoic Acid Signal

Abstract: Quorum sensing (QS) signals are widely used by bacterial pathogens to control biological functions and virulence in response to changes in cell population densities. Burkholderia cenocepacia employs a molecular mechanism in which the cis-2-dodecenoic acid (named Burkholderia diffusible signal factor [BDSF]) QS system regulates N-acyl homoserine lactone (AHL) signal production and virulence by modulating intracellular levels of cyclic diguanosine monophosphate (c-di-GMP). Thus, inhibition of BDSF signaling may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…We initially focused our attention on B. cenocepacia CepIR because this QS system solely controls pathogenicity in C. elegans where the virulence attenuation of PAA degradation mutants was first characterized (22). However, current evidence suggests that a two-component system, RqpSR, is at the top of the hierarchy controlling both AHL-and Burkholderia diffusible signal factor (BDSF)-dependent QS systems (39,40). The BDSF-dependent system uses cis-2-dodecenoic acid signaling molecule (BDSF) that regulates overlapping genes with the AHL QS system (41).…”
Section: Discussionmentioning
confidence: 99%
“…We initially focused our attention on B. cenocepacia CepIR because this QS system solely controls pathogenicity in C. elegans where the virulence attenuation of PAA degradation mutants was first characterized (22). However, current evidence suggests that a two-component system, RqpSR, is at the top of the hierarchy controlling both AHL-and Burkholderia diffusible signal factor (BDSF)-dependent QS systems (39,40). The BDSF-dependent system uses cis-2-dodecenoic acid signaling molecule (BDSF) that regulates overlapping genes with the AHL QS system (41).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies reported that fatty acids exhibit anti‐hyphal and antibiofilm activities at concentrations less than their MICs (Kumar et al ., 2020). For example, several fatty acids have been shown to selectively disrupt or inhibit biofilm formation by various microbial pathogens, such as Staphylococcus aureus (Davies and Marques, 2009; Kim et al ., 2018), Pseudomonas aeruginosa (Inoue et al ., 2008; Wenderska et al ., 2011), Candida albicans (Murzyn et al ., 2010; Muthamil et al ., 2018; Prasath et al ., 2019), and others (Wenderska et al ., 2011; Santhakumari et al ., 2017; Ramanathan et al ., 2018; Cui et al ., 2019). More specifically, capric acid (10:0) and lauric acid (12:0) inhibit the growth of planktonic Candida cells (Bergsson et al ., 2001), and butanoic acid (4:0) inhibit hyphal formation by C. albicans (Noverr and Huffnagle, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In Burkholderia cenocepacia , DSF diffuse across the membrane to bind to cytosolic proteins to activate transcriptional changes ( Suppiger et al, 2016 ). Cui et al (2019) developed a DSF analog that was capable of interfering with Burkholderia cenocepacia quorum sensing and virulence, demonstrating its potential as a novel antibacterial agent. Similarly, Huedo et al (2019) developed DSF that could interfere with quorum sensing of both Stenotrophomonas maltophilia and Burkholderia cepacia .…”
Section: Discussionmentioning
confidence: 99%